Peranan Revolusi Industri 4.0 Terhadap Mutu Pendidikan Sekolah Menengah Kejuruan Jurusan Akuntansi - Tony Soebijono; Martinus Sony Erstiawan (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2020)
he Prapanca 2 Surabaya Vocational High School (SMK) majoring in accounting is one entity that is willing to compete and is skilled and professional inwelcoming the Industrial Revolution 4.0. So far, the principal has prepared a strategy to improve the quality of graduates to suit the needs of the businessmarket (Business World (DU)/Industrial World (DI)). Some of the strategies used in aligning education with the demands of the 4.0 Industrial Revolution erainclude improving the quality of sarpras (facilities and infrastructure) in the learning process based on industrial needs (Link and Match) during the IndustrialRevolution 4.0 period, the fulfillment of DU/DI standard facilities and infrastructure and increasing teacher competence is focused on the era of theIndustrial Revolution 4.0. The role of the principal has a point of view broad, open, disciplined, firm, and committed.